Big data and academic libraries: is it big for something or big for nothing?. Issue 2 (4th January 2021) - Tella, Adeyinka; Kadri, Kehinde Khadijat
Abstract : Purpose: The paper examined big data and academic libraries and emphasized whether it is big for something or nothing. Design/methodology/approach: A conceptual and review analysis of documents was adopted to determine the concept of big data, the sources, the features, the relevance to academic libraries, specific case studies from around the world that have made use of big data, uses of big data in academic libraries, a review of best practices in the use of big data in academic libraries and the challenges. Findings: The paper reports that although big data is indeed very big in academic libraries because there are evidences of its adoption and best practices in its use in academic libraries across the world, available challenges can render it big for nothing. Research limitations/implications: This study is limited in terms of using literature review approach to discuss big data and academic libraries. The study is also limited in terms of focusing academic libraries and not taken other types of libraries into consideration. Practical implications: The study has created awareness on the part of academic libraries stakeholders including authorities, librarians and users on the relevance of big data in academic and how big indeed it is in academic library landscape. The study also implied future related studies can borrow ideas from the current studies, which will inform whether an empirical evaluation is possible on the subject matter. Originality/value: The paper is the original idea by the author, and it is to emphasize the relevance of big data in academic libraries and to prepare academic libraries that have not been tapping the opportunities of big data to get ready.